2000
DOI: 10.1021/es001445q
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Equilibria Model of Strontium-90 Adsorption and Transport in Soil in Response to Dynamic Alkaline Conditions

Abstract: Strontium-90 is a major hazardous contaminant of radioactive wastewater and its processing sludges at many Department of Energy (DOE) facilities. In the past, such contaminated wastewater and sludge have been disposed in soil seepage pits, lagoons, or cribs often under highly perturbed alkaline conditions (pH > 12) where 90Sr solubility is low and its adsorption to surrounding soil is high. As natural weathering returns these soils to near-neutral or slightly acidic conditions, the adsorbed and precipitated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Conversely, a rapid surge in the sorption capacity of Sr 2+ was observed above pH 10, which is most likely related to the formation of Sr­(OH) 2 ( K sp = 6.4 × 10 –3 ). However, the solution data indicates the decrease in the concentration of dissolved Mg 2+ at this region, which informs the possibility of the co-precipitation of Sr 2+ with Mg 2+ as Mg­{Sr}­(OH) 2 . Similar observations were demonstrated on the C-dot-decorated MgAl-LDH nanocomposites during Sr 2+ sorption .…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Conversely, a rapid surge in the sorption capacity of Sr 2+ was observed above pH 10, which is most likely related to the formation of Sr­(OH) 2 ( K sp = 6.4 × 10 –3 ). However, the solution data indicates the decrease in the concentration of dissolved Mg 2+ at this region, which informs the possibility of the co-precipitation of Sr 2+ with Mg 2+ as Mg­{Sr}­(OH) 2 . Similar observations were demonstrated on the C-dot-decorated MgAl-LDH nanocomposites during Sr 2+ sorption .…”
Section: Resultssupporting
confidence: 74%
“…However, the solution data indicates the decrease in the concentration of dissolved Mg 2+ at this region, which informs the possibility of the co-precipitation of Sr 2+ with Mg 2+ as Mg{Sr}(OH) 2 . 41 Similar observations were demonstrated on the C-dot-decorated MgAl-LDH nanocomposites during Sr 2+ sorption. 6 The removal capacity of SeO 4 2− was almost maintained in the broad pH range of 3−10 (Figure 8A) due to the alkalization of the solution by the dissolution of Mg 2+ to maintain the equilibrium pH (Figure 8B).…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…The critical analysis of the solution data revealed that the increase in the pH of the medium as well as decrease in the dissolved Mg 2+ concentration was observed at this region. Based on the observations it can be concluded that the Sr 2+ was partially coprecipitated with Mg 2+ as Mg­{Sr}­(OH) 2 , which may be the reason for such enhanced Sr 2+ adsorption from the solution . At lower pH of the medium higher dissolution Mg 2+ occurs from solid for the alkalization of solution and it was precipitated with Sr 2+ at higher pH (Figure B).…”
Section: Resultsmentioning
confidence: 93%
“…Thirdly, 85 Sr in untreated soil behaved as expected for a cation-exchangeable species in soil. Over several months, the dissolved cations in stream water replaced most, but not all, of the 85 Sr resulting in an expected degree of equilibration over time given the soil's cation exchange capacity and the concentration of dissolved cations in stream water (Spalding and Spalding 2001). Some of the spiked 85 Sr (about 8%) in the untreated soil appeared to be naturally attenuated and remained strongly adsorbed to the soil.…”
Section: Resultsmentioning
confidence: 99%